Ruthenium-Tin Oxide/Carbon Supported Platinum Catalysts for Electrochemical Oxidation of Ethanol in Direct Ethanol Fuel Cells. Issue 3 (1st January 2018) - James, David D.; Moghaddam, Reza B.; Chen, Binyu; Pickup, Peter G.
Abstract : Carbon black coated with a mixture of Ru and Sn oxides has been used as a support for Pt nanoparticles (Pt/Ru-Sn oxide/C) in order to increase their activity for ethanol oxidation without a significant loss of selectivity. The mixed oxide layer was prepared by the reaction of the carbon surface with KRuO4 in the presence of Sn(IV). Pt nanoparticles were then deposited by reduction of H2 PtCl6 with NaBH4 . The resulting catalyst provided higher electrochemical activities than Pt black for ethanol oxidation in both a liquid electrolyte cell at ambient temperature and a proton exchange membrane direct ethanol fuel cell at 80°C. CO2 yields from the fuel cell were similar for the Pt/Ru-Sn oxide/C and Pt black catalysts, while acetic acid to acetaldehyde ratios were much higher for Pt/Ru-Sn oxide/C. Consequently, the Pt/Ru-Sn oxide/C catalyst increased both the voltage efficiency and faradaic efficiency of the cell.